Effect of fertilizer-N and organic resource management on soil aggregates formation and carbon cycling in the central highlands of Kenya - NJOROGE, KINYANJUI SAMUEL; NJIRU, DANIEL MUGENDI; VANLAUWE, BERNARD (Society for Indonesian Biodiversity & Universitas Mulawarman, Samarinda, Indonesia, 2018)
Njoroge KS, Mugendi DN, Vanlauwe B. 2018. Effect of fertilizer-N and organic resource management on soil aggregates formation and carbon cycling in the central highlands of Kenya. Asian J Agric 2: 25-37. To inquire the way the alteration of soils of various textures and fertility values with fertilizer-N and organic resources influencing aggregate formation and subsequent carbon (C) cycling in aggregates became the objective of this research. The experiment was carried out in Embu and Machang'a regions of central Kenya and was rooted on a putrefaction tube experiment that was established in April 2005. This experiment was intended at completing long-term field experimentations initiated in 2002 to set up the impact of the application of various combinations of organic and mineral resources on soil nutrient status. The main variables were fertilizer-N and organic resources, with the sub-management being soil fertility values. Maize stover and urea fertilizer were mixed with 3.2 kg of soil and put in putrefaction tubes. The implementation rate was 4 ton and 120 kg per hectare for the maize stover and fertilizer respectively. Four management were developed, namely: control (no organic resources or fertilizer-N added), lone fertilizer-N, lone stover, and combined stover and fertilizer-N, with each management having three replicates. To decide the alterations in soil aggregates, dirt samples acquired from the putrefaction tubes were fractionated through wet sieving. SOM fractionation was also carried out to gain the various SOM fractions. All achieved aggregates and SOM fractions were then dried in the oven, ground, and analyzed for C. All collected data were examined with the PROC MIXED procedure of SAS and the means separated at p <0.05. Bigger quantity of macroaggregates from Embu soils was studied than that from Machang'a soils. For both Embu and Machang'a soil, the alteration of soils with lone or combined fertilizer-N and organic resources had a notable impact (p <0.05) on the portions of all aggregate class sizes. The alteration of soils of various fertility values with lone or combined fertilizer-N and organic resources also had a notable impact on the allocation of SOM fractions for both Embu and Machang' soils. Remarkable discrepancies in whole soils, aggregates and SOM fractions percentage carbon values were also studied. On the whole, the silt and clay fraction had higher C values than that in other aggregate size classes representing higher stabilization of C within this fraction. From the results of this research, it is concluded that the utilization of combined organic and mineral resources is preferred for the enhancement and the preservation of soil fertility in high fertility soils. In low fertility coarse-textured soils, the lone implementation of organic resources is suggested for the enhancement and the preservation of soil fertility.